Hospital admission in children and adolescents with or without type 1 diabetes from Germany: An analysis of statutory health insurance data on 12 million subjects. Issue 4 (11th December 2017) - Bohn, Barbara; Schwandt, Anke; Ihle, Peter; Icks, Andrea; Rosenbauer, Joachim; Karges, Beate; Holl, Reinhard W
Abstract : Objective: To compare the chance of hospital admissions in children and adolescents with type 1 diabetes (T1D) to that without T1D from Germany. Methods: Data were provided by the German information system for health care data which contains information on all patients with a statutory health insurance. The years 2009 and 2011 were considered. Children and adolescents (0 to ≤19 years of age; n = 12 030 242) were included. Unadjusted odds ratios (ORs) with 95% confidence interval (95% CI) were used to compare the hospitalization rate for patients with ( n = 26 444) or without T1D (12 003 798). T1D was identified by documented insulin treatment and by ICD‐code E10/14. Results were stratified by age‐group (0‐5; >5‐10; >10‐15, >15‐19 years) and gender. Results: In all age‐groups, the hospitalization chance in patients with T1D was higher compared to that of their peers (database 2011). The highest OR was observed in >5 to 10‐year‐old patients (OR 8.1; 95% CI: 7.7‐8.5), followed by patients >10 to 15 years (OR 7.4; 95% CI: 7.1‐7.7) and patients ≤5 years (OR 5.3; 95% CI: 4.8‐5.7). The lowest OR was present in patients >15 to 19 years (OR 4.0; 95% CI: 3.9‐4.2). Overall, OR for hospital admission were higher in girls with T1D compared to boys. The most frequent reasons for hospitalization in T1D were "T1D without complications" (68.4%) and "T1D with ketoacidosis" (18.6%). Conclusions: Children and adolescents with T1D in Germany had a 4 to 8 times higher hospitalization chance compared to children without T1D. The OR in T1D patients compared to peers were higher in girls than in boys. High rates of elective hospital admission in Germany may contribute to these results.